IS4AC (Intelligence System for Air Controller) Application for Air Quality Control of Tobacco Storage Warehouse PT. Mangli Djaya Raya - Riskiawan, Hendra Yufit; Utomo, Denny Trias; Setyohadi, Dwi Putro Sarwo; Firgiyanto, Refa; Firmansyah, Muhammad Hafidh; Widiawan, Beni; Agustianto, Khafidurrohman; Hakim, Thoriq Lukman; Akhdiar, Fikri (P3M Politeknik Negeri Jember, 2025)
Warehouse Quality Monitoring Information System (IS4AC) was developed to improve the monitoring of storage environmental conditions, especially related to temperature, humidity, and PH₃ levels, which have an impact on product quality. This study includes the collection of initial data from partners used for system design and modeling, followed by the development of a sensor-based application that allows real-time monitoring. The research methodology includes data collection, system design, application development, and testing and implementation in the laboratory and partner warehouse locations. The results of the study show that IS4AC is able to provide accurate and timely information, improve operational efficiency, and reduce the risk of product damage due to unmonitored environmental conditions. With this system, users can make better decisions in storage quality management. In conclusion, this study shows the significant potential of an automated monitoring system in improving warehouse management, as well as contributing to the development of adaptive technology in various industrial sectors.